ANALISIS PENGEMBANGAN PEGAWAI NEGERI SIPIL PADA KANTOR BADAN KEPEGAWAIAN DAERAH KABUPATEN KUTAI TIMUR - Dio, Jeffry Alif (PREDIKSI, 2016)
This study aims to determine and describe the employee development program in the Office of the Regional Employment Board of East Kutai Regency. The approach used in this study is a qualitative descriptive approach. The results showed that the implementation of staff development at the Regional Employment Board of East Kutai Regency has an average value of 81.23% and the percentage of this result is in the interval 76% - 100%, which means the implementation of employee development fit in either category. Thus, the hypothesis formulated in this study can be received and verified.Â